The role of social relatedness and self-beliefs in social functioning in first-episode psychosis: Are we overestimating the contribution of illness-related factors?. (2020) - González-Blanch, César; Medrano, Leonardo A.; Bendall, Sarah; D'Alfonso, Simon; Cagliarini, Daniela; McEnery, Carla; O'Sullivan, Shaunagh; Valentine, Lee; Gleeson, John F.; Alvarez-Jimenez, Mario
Abstract: Objective: Numerous research studies have demonstrated an association between higher symptom severity and cognitive impairment with poorer social functioning in first-episode psychosis (FEP). By contrast, the influence of subjective experiences, such as social relatedness and self-beliefs, has received less attention. Consequently, a cohesive understanding of how these variables interact to influence social functioning is lacking. Method: We used structural equation modeling to examine the direct and indirect relationships among neurocognition (processing speed) and social cognition, symptoms, and social relatedness (perceived social support and loneliness) and self-beliefs (self-efficacy and self-esteem) in 170 individuals with FEP. Results: The final model yielded an acceptable model fit ( χ 2 = 45.48, comparative fit index = 0.96; goodness of fit index = 0.94; Tucker–Lewis index = 0.94; root mean square error of approximation = 0.06) and explained 45% of social functioning. Negative symptoms, social relatedness, and self-beliefs exerted a direct effect on social functioning. Social relatedness partially mediated the impact of social cognition and negative symptoms on social functioning. Self-beliefs also mediated the relationship between social relatedness and social functioning. Conclusions: The observed associations highlight the potential value of targeting social relatedness and self-beliefs to improve functional outcomes in FEP. Explanatory models of social functioning in FEP not accounting for social relatedness and self-beliefs might be overestimating the effect of the illness-related factors.